Risk factors for canine parvovirosis in four localities of Cuba - Peña G., Iván (2020)
The study aimed to determine the risk factors associated with the presentation of canine parvovirosis (CPV) in four locations in Cuba. The work was carried out between September 2018 and March 2019 with 87 canines of different breeds and ages, positive or not for CPV, in the municipalities of Ciego de Ávila, Camagüey, Morón and Gaspar (Cuba). The association measures [Odds ratio] (OR) of the possible irrigation factors to contract canine parvovirosis were determined. The risk factors associated with CPV with statistical significance were type of feeding and vaccination.